The role of merchants in the linguistic history of the Sephardic Jews - Minervini, Laura (RiCOGNIZIONI. Rivista di Lingue e Letterature straniere e Culture moderne, 2020)
The article deals with the merchants’ contribution to the history of Sephardic Spanish (Ladino). It examines some samples of merchants letters (15th-18th c.) and surveys their general patterns, which were relatively stable through the centuries. Moreover, it sketches the role of the merchants as a social group first in the diffusion and normativization of the Sephardic vernacular, and later in its confrontation with Western European languages.